Golda [videorecording (DVD)] - Martin, Nicholas; Mirren, Helen; Cottin, Camille; Ashkenazi, Lior; Heuberger, Rami; Keinan, Rotem, 1979-; Benedeḳ, Devir, 1969-; Piercy, Ellie; Goodman, Henry, 1950-; Stoppard, Ed; Mafham, Dominic; Knoller, Ohad, 1976-; et al. (Decal Releasing, LLC, 2023)
On October 6th, 1973, under cover of darkness, on Israel's holiest day and during the month of Ramadan, the combined forces of Egypt, Syria, and Jordan begin a surprise attack on the Sinai Peninsula and the Golan Heights. Outnumbered and outgunned, Israel's only female Prime Minister, Golda Meir, confronts the immediate, clear, and present danger of a ticking timebomb that she hoped never to face. Surrounded, isolated, and frustrated by the infighting of her all-male cabinet, with little hope of rescue, one woman is in a race against time to save millions of lives on both sides of the conflict.